Good girls and wicked witches : women in Disney's feature animation - Davis, Amy M. (Amy Michele) (John Libbey Publishing ; Distributed in North America by Indiana University Press, 2006)
In Good Girls and Wicked Witches, Amy M. Davis re-examines the notion that Disney heroines are rewarded for passivity. Davis proceeds from the assumption that, in their representations of femininity, Disney films both reflected and helped shape the attitudes of the wider society, both at the time of their first release and subsequently. Analyzing the construction of (mainly human) female characters in the animated films of the Walt Disney Studio between 1937 and 2001, she attempts to establish the extent to which these characterizations were shaped by wider popular stereotypes. Davis argues th.